2016
DOI: 10.1016/j.fsi.2015.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular importance of prawn large heat shock proteins 60, 70 and 90

Abstract: Considering the importance of heat shock proteins (HSPs) in the innate immune system of prawn, a comparative molecular approach was proposed to study the crustacean large HSPs 60, 70 and 90. Three different large HSPs were identified from freshwater prawn Macrobrachium rosenbergii (Mr) cDNA library during screening. The structural and functional characteristic features of HSPs were studied using various bioinformatics tools. Also, their gene expression and mRNA regulation upon various pathogenic infections was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…Three more cDNA sequences encoding heat shock proteins such as HSP60 (HG001456), HSP70 (HG001455) and HSP90 (HG001457) were also identified from M. rosenbergii cDNA library (Chaurasia et al . ).…”
Section: Immune Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…Three more cDNA sequences encoding heat shock proteins such as HSP60 (HG001456), HSP70 (HG001455) and HSP90 (HG001457) were also identified from M. rosenbergii cDNA library (Chaurasia et al . ).…”
Section: Immune Systemmentioning
confidence: 97%
“…; Chaurasia et al . b), anti‐lipopolysaccharide factor (Arockiaraj et al . ) and lectin (Arockiaraj et al .…”
Section: Immune Systemmentioning
confidence: 99%
“…In the previous studies, MjHSP60 was found to be mainly expressed in defence and digestive tissues including the hepatopancreas, haemocytes, gills and the stomach, which are in direct contact with the external environment and are more vulnerable to invading pathogens and exogenous compounds (Chaurasia et al., ; Yang et al., ; Zhou, Wang, He, et al., ; Zhou, Wang, Xin, et al., ). In our study, MjHSP60 was ubiquitously expressed in all examined tissues of M .…”
Section: Discussionmentioning
confidence: 94%
“…HSP60 is a major node in the intracellular chaperone network and plays a crucial role in stress response, especially in heat stress (Chaurasia et al., ; Quintana & Cohen, ; Shi et al., ; Xu et al., ; Xu & Qin, ; Yang et al., ; Zhou, Wang, Xin, et al., ). In this study, the expression level of MjHSP60 in both gills and hepatopancreas of M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation